P062: Designing team success - an engineering approach to capture team procedural steps to develop microskills for interprofessional skills education. (May 2019) - Hanlon, R.; French, J.; Atkinson, P.; Fraser, J.; Benjamin, S.; Poon, J.
Abstract : Introduction : Chest tube insertion, a critical procedure with a published complication rate (30%), is a required competency for emergency physicians. Microskills training has been shown to identify steps that require deliberate practice. Objectives were: 1. Develop a chest tube insertion microskills checklist to facilitate IPE, 2. Compare the microskills checklist with published best available evidence, 3. Develop an educational video based on the process map, 4. Evaluate the video in an interprofessional team prior to cadaver training as a proof of concept.Methods : The study was conducted between March 2018 and November 2018. An initial list of process steps from the best available evidence was produced. This list was then augmented by multispecialty team consensus (3 Emergency Physicians, 1 Thoracic Surgeon, 1 medical student, 2 EM nurses). Two prototyping phases were conducted using a task trainer and a realistic interprofessional team (1 EM Physician, 1 ER Nurse, 1 Medical student). A final microskills list was produced and compared to the procedural steps described in consensus publications. An educational video was produced and evaluated by an interprofessional team prior to cadaver training using a survey and Likert scales as a proof of concept. Participants were 7 EM RNs and 6 ATLS trained physicians. Participants were asked to fill out a nine-question survey, using a 5-point Likert Scale (1-strongly disagree to 5 strongly agree).Results : The final process map contained 54 interdisciplinary steps, compared to ATLS that describes 14 main steps and peer reviewed articles that describe 9 main steps. The microskills checklist described, in more detail, the steps that relate to team interaction and the operational environment. Physicians rated the training video were able to apply what they learned in the video with an average of 4.67 (median of 5, mode of 5, and an IQR of 0.75).Conclusion : The development of the process maps and microkills checklists provides interprofessional teams with more information about chest tube insertion than instructions described in commonly available courses and procedural steps derived by consensus.